Schooling and identification processes in intercultural contexts (Praxis Educativa, 2020)
The article recovers some reflections on the socio-educational trajectories of a group of indigenous teachers in the province of Chaco, emphasizing schooling and the processes of identification of the subjects. This work is part of a broader investigation focused on systematizing these trajectories considering the processes of articulation / overlap / identity denial of a group of qom teachers in the center of the province. The methodology was based on the ethnographic perspective and we incorporated some contributions of the methodological resource of the auto-biographical account. That is, we conduct in-depth interviews, participant observations, informal talks with multiple educational agents, as well as autobiographical accounts with numerous qom teachers in the region.
Keywords: indigenous teachers; schooling; identification processes; socioeducational trajectories; diversity.